Bureaucracy and society in transition : comparative perspectives - Byrkjeflot, Haldor; Engelstad, Fredrik, 1944- (Comparative social research, 2018)
Despite criticism of inefficiencies and unlimited growth, bureaucracies still fill crucial positions in modern societies. This volume examines 'varieties in bureaucracies' across Europe, with a specific focus on the Nordic region.